AI Diffusion: An Android Application for Text-to-Image Generation Using Generative AI Models - Agrawal, Anant; Vardhan Rathour, Vedant; Babeetha, S (International Journal of Computer Sciences and Engineering, 2025)
AI Diffusion is an Android-supported text-to-image synthesis application fusing cutting-edge generative artificial intelligence and the pervasiveness of Android platforms. The vision is to provide users with a simple yet incredibly powerful tool with which they can produce realistic and imaginative images from text-based descriptions. Application architecture features an Android frontend developed with Kotlin and Python-based backend authored in FastAPI. Upon entering a prompt by a user, the backend interacts with a pre-trained generative AI model hosted via API to create an associated image, which is then rendered inside the app. The system is optimized to be lean and responsive to support real-time interaction even on resource-constrained devices. Comprehensive testing shows that the app works seamlessly with minimal latency and creates contextually accurate images for all types of prompts. The project bridged the distance between powerful AI functionality and genuine mobile usability, bringing more individuals access to creative tools and enabling them to access them with more ease. The project also enables future upgrade prospects, such as customization options and offline model suitability, to add more feasibility to mobile AI solutions.